Implementation of National Identity Through History: Building Human Sustainability in the Young Generation - Mohd Tohar, Siti Nor Azhani; Ani, Fauziah; Razali, Asbah (Journal of Techno-Social, 2019)
These days, the void in appreciating the national history is becoming more apparent especially among the younger generation. This issue should be taken seriously as history is an important mechanism for the implementation of national identity of the multi-ethnic community in Malaysia. Thus, this paper discusses the relationship between history and national identity, the disparity of the younger generation in appreciating history and the measurement mechanisms for the appreciation of the history of the country. This discussion is based on content analysis of relevant literature materials. The results of this discussion need to be highlighted as history is often disregarded by most communities in the face of modernity. The significance of history should be emphasized as a thrust to the adoption of national identity in the community and to build human sustainability for the survival of future civilizations in Malaysia. Keywords: history, national identity, young generation, human sustainability, measurement of history appreciation